Impact of an external electron acceptor on phosphorus mobility between water and sediments - Martins, Gilberto (2014)
The present work assessed the impact of an external electron acceptor on phosphorus fluxes between water-sediment interface. Microcosm experiments simulating a sediment microbial fuel cell (SMFC) were carried out and phosphorus was extracted by an optimized combination of three methods. Despite the low voltage recorded, ∼96 mV (SMFC with carbon paper anode) and ∼146 mV (SMFC with stainless steel scourer anode), corresponding to a power density of 1.15 mW/m2 and 0.13 mW/m2, it was enough to produce an increase in the amounts of metal bound phosphorus (14% vs 11%), Ca-bound phosphorus (26% vs 23%) and refractory phosphorus (33% vs 28%). These results indicate an important role of electroactive bacteria in the phosphorus cycling and open a new perspective for preventing metal bound phosphorus dissolution from sediments.